Mass media in conflict. Thoughts on the role of journalism in the bolivian situation - Torrico-Villanueva, Erick R. (2009)
Bolivian mass media are living a credibility crisis caused by politization, the frequent use of sensationalism and their common professional mistakes. These characteristics have been increased in today’s highly conflictive democratic reorganization times. Media were narrators but became real actors of political conflicts. For this reason, and in the context of a polarized society, media are also turning into victims or instruments of clashes. Their challenge now is to endeavour for the development and practice of a true democratic culture.